Analisis Kinerja Perusahaan Menggunakan Metode Balance Scorecard Pada PT Berkat Anugerah Plasindo Pratama : Company Performance Analysis Using the Balance Scorecard Method at PT Berkat Anugerah Plasindo Pratama - Yenny Suheni; Usran Masahere (CV Warnak Johanna Nusantara, 2026)
In facing increasingly competitive business conditions, every company needs an effective performance measurement system to remain competitive and achieve long-term goals. This study aims to analyze the performance of PT. Berkat Anugerah Plasindo Pratama using the Balanced Scorecard (BSC) method developed by Kaplan and Norton. The Balanced Scorecard evaluates organizational performance through four main perspectives: financial, customer, internal business processes, and learning and growth. This research applies a descriptive quantitative approach, focusing on PT. Berkat Anugerah Plasindo Pratama, a company engaged in the plastic manufacturing industry. The data were collected through observation, interviews, and documentation during the period of October to December 2025. The analysis results indicate that the company performs well in financial and customer perspectives but requires improvement in internal business process efficiency and human resource development. The implementation of the Balanced Scorecard is expected to assist the company in evaluating performance comprehensively, identifying supporting and inhibiting factors, and providing a foundation for strategic decision-making. Through continuous evaluation using the BSC approach, the company can enhance effectiveness, efficiency, and competitiveness in the plastic manufacturing industry